2014
DOI: 10.1016/j.envres.2014.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in residential dust and risk of childhood acute lymphoblastic leukemia

Abstract: Several polycyclic aromatic hydrocarbons (PAHs) are known or probable human carcinogens. We evaluated the relationship between PAH exposure and risk of childhood acute lymphoblastic leukemia (ALL) using concentrations in residential dust as an exposure indicator. We conducted a population-based case-control study (251 ALL cases, 306 birth-certificate controls) in Northern and Central California from 2001–2007. We collected residential dust using a high volume small surface sampler (HVS3) (n=185 cases, 212 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…In our study, we have found high statistically significant excess risks in children living close to industrial installations releasing these pollutants, findings consistent with other studies about exposure to specific PAHs (Deziel et al, 2014;Miligi et al, 2013). With respect to other pollutants, a Canadian study found an association between exposure to zinc in drinking water and childhood leukemia (Infante-Rivard et al, 2001), whereas some studies have found associations between some types of childhood leukemia and parental occupational exposure to toluene (Infante-Rivard et al, 2005), and chromium and lead (Miligi et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we have found high statistically significant excess risks in children living close to industrial installations releasing these pollutants, findings consistent with other studies about exposure to specific PAHs (Deziel et al, 2014;Miligi et al, 2013). With respect to other pollutants, a Canadian study found an association between exposure to zinc in drinking water and childhood leukemia (Infante-Rivard et al, 2001), whereas some studies have found associations between some types of childhood leukemia and parental occupational exposure to toluene (Infante-Rivard et al, 2005), and chromium and lead (Miligi et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Although some modification in genome, like gene NOTCH1 [2], TEL-AML1 [3], Philadelphia chromosome [4], and exposure to carcinogenic factors, like aromatic hydrocarbons [5], ionizing radiation [6], air pollution [7] have been described to influence the ALL pathogenesis, they explain a few percentage of the cases.…”
Section: Introductionmentioning
confidence: 98%
“…Although prior research has quantified levels of exposure and subsequent potential health implications of PAHs in many occupational settings (Bosetti, Boffetta, and La Vecchia 2007; Langlois et al 2013; Lupo et al 2012; O’Brien et al 2016), more information is needed to quantify domestic exposures and their potential health impacts (DellaVale et al 2016; Deziel et al 2014; Kang et al 2015; Kim, Jahan, Kabir, and Brown 2013; Kuo, Hsu, and Lee 2003). Settled dust and particulate matter within homes can be an important exposure route for individuals, in general, and children, in particular.…”
Section: Introductionmentioning
confidence: 99%